Эпидермальные эноциты, связанные с хеморецепторами максиллярных щупиков самцов кровососущих комаров - Смолина, Н.А. (Вестник зоологии, 1982)
Ultrastructure of the epidermal oenocytes connected with chemosensory areas of the palpae maxillares cuticular elements have been studied in Culisetaannulata imago males. The studied cells are suggested to bear the function of cuticular sclerotization and to produce certain sorption layer components of the chemoreceptors' cuticular part.